How Agricultural Intensification Affects Biodiversity and Ecosystem Services - Bommarco, Riccardo; Eggers, Sönke; Pärt, Tomas; Bengtsson, Jan (Advances in Ecological Research, 2016)
As the world's population continues to grow, the demand for food, fodder, fibre and bioenergy will increase. In Europe, the Common Agricultural Policy (CAP) has driven the intensification of agriculture, promoting the simplification and specialization of agroecosystems through the decline in landscape heterogeneity, the increased use of chemicals per unit area, and the abandonment of less fertile areas. In combination, these processes have eroded the quantity and quality of habitat for many plants and animals, and hence decreased biodiversity and the abundance of species across a hierarchy of trophic levels and spatial scales within Europe. This biodiversity loss has led to profound changes in the functioning of European agroecosystems over the last 50 years. Here, we synthesize the findings from a large-scale pan-European investigation of the combined effects of agricultural intensification on a range of agroecosystem services. These include (1) the persistence of high conservation value species; (2) the level of biological control of agricultural pests and (3) the functional diversity of a number of taxonomic groups, including birds, beetles and arable weeds. The study encompasses a gradient of geography-bioclimate and agricultural intensification that enables the large-scale measurement of ecological impacts of agricultural intensification across European agroecosystems. We provide an overview of the role of the CAP as a driver of agricultural intensification in the European Union, and we demonstrate compelling negative relationships between the application of pesticides and the various components of biodiversity studied on a pan-European scale.